Epioptics-11 : Proceedings of the 49th Course of the International School of Solid State Physics. - Cricenti, Antonio (Science and Culture Series - Physics., 2012)
The book is aimed at assessing the capabilities of state-of-the-art optical techniques in elucidating the fundamental electronic and structural properties of semiconductor and metal surfaces, interfaces, thin layers, and layer structures, and assessing the usefulness of these techniques for optimization of high quality multilayer samples through feedback control during materials growth and processing. Particular emphasis is dedicated to the theory of nonlinear optics and to dynamical processes through the use of pump-probe techniques together with the search for new optical sources. Some new a.